PENGARUH KESADARAN KESEHATAN, NILAI YANG DIRASAKAN, KEAMANAN PANGAN DAN HARGA TERHADAP NILAI BELI ULANG PADA KONSUMEN PIZZA HUT DI KOTA BANDA AC - M Rizkal Ramadhan; Sorayanti Utami (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
The purpose of this case study is to find out "The Influence of Health Consciousness, Perceived Value, Food Safety and Price on Purchase Intentions at Pizza Hut Banda Aceh” the sample of respondents in this study used criteria, namely the people of Banda Aceh, who visited Pizza Hut Banda Aceh. This research method used questionnaire as research instrument. The questionnaires were successfully analyzed as many as 128 questionnaires. Sampling technique used is non probability sampling, this technique is used because profitability of elements in the population to be selected as the sample is not known. Multiple Linear Regression is used as an analytical method to determine the effect of the variables involved. Based on the results of data analysis showed that Health Consciousness variable was found to have less impact on customer purchase intention of Pizza Hut. This is because the consumers could be looking on other variables such as Perceived Value, Food Safety and Price in deciding to purchase Pizza Hut products. We suggest that Pizza Hut needs to pay attention for Health Consciousness variable, it will grow they market from costumer who care about healthy lifestyle.